Amino acid abundances and compositions in iron and stony‐iron meteorites. (25th March 2021) - Elsila, Jamie E.; Johnson, Natasha M.; Glavin, Daniel P.; Aponte, José C.; Dworkin, Jason P.
Abstract: The organic compositions of carbonaceous chondrite meteorites have been extensively studied; however, there have been fewer reports of other meteorite classes, and almost none from iron meteorites, which contain much less carbon than carbonaceous chondrites but make up ~4% of observed meteorite falls. Here, we report the bulk amino acid content of three iron meteorites (Campo del Cielo, IAB; Canyon Diablo, IAB; and Cape York, IIIAB) and both the metal and silicate portions of a pallasite (Imilac). We developed a novel method to prepare the samples for analysis, followed by hot water extraction and analysis via liquid chromatography‐mass spectrometry. Free amino acid abundances ranging from 301 to 1216 pmol g −1 were observed in the meteorites, with the highest abundance in the silicate portion of the pallasite. Although some of the amino acid content could be attributed to terrestrial contamination, evidence suggests that some compounds are indigenous. A suite of C5 amino acids was observed with a distinct distribution favoring a straight chain ( n ‐pentanoic acid) structure; this straight chain dominance is suggestive of that observed in thermally altered stony meteorites. Amino acids were also observed in terrestrial iron granules that were milled and analyzed in the same way as the meteorites, although the distribution of detected amino acids was different. It is possible that similar formation mechanisms existed in both the meteorites and the terrestrial iron, or that observed amino acids resulted from reactions of precursors during sample preparation. This work suggests that iron meteorites should not be overlooked for contributions of amino acids and likely other soluble organic molecules to the early Earth. Future studies of iron–nickel meteorites and asteroids, such as Psyche, may provide further insights into their potential organic inventory.